THE AESTHETIC OF COLOR EXPRESSION IN THE SELECTED WORKS OF THE STUDENTS OF ARTISTIC EDUCATION DEPARTMENT IN CERAMIC - Asst. Prof. Dr. Ammar Jabbar Hussein Al-wahaj (American Journals Publishing, 2023)
The aims of study to reveal the beauty of color expression in the works of the Department of Art Education. To assure us of the importance of glazed pottery, a view that lies in its bearing of colors that excite the viewer. Therefore, its importance comes from revealing the color beauty placed on the surface of the pottery vessels, which are basic components for working with (ceramic) a word. Commercial It is one of the lessons taught by students of art faculties, art education departments and art institutes. In the second chapter, the researcher to explain the philosophy of beauty, as well as introducing the pottery kiln or the art of ceramics, which is a disclosure of the most important philosophies of beauty. In the third chapter, the researcher dealt with the analysis of the students' work and revealed the expression of these colors that cover the artistic works accomplished by the students of the art education departments. As results and conclusions appeared in the fourth chapter explaining to us the most important of these works of art.